Budaya Suku Sasak Memoderasi Gaya Kepemimpinan, Independensi, Pemahaman Good Governance Pada Kinerja Auditor - Pituringsih, Endar; Basuki, Prayitno; Akram, Akram (E-Jurnal Akuntansi, 2022)
This study aims to examine the influence of lokal culture of Sasak auditors as a moderating influence of leadership style, independence and understanding of good governance on the performance of internal auditors. The study population was all auditors who carried out inspections at the Inspectorate of the entire island of Lombok, as many as 215 people. The sampling technique used was purposive sampling. From these criteria, a research sample of 129 auditors was obtained. The analytical tool used in the research is Moderated Regression Analysis (MRA) with SPSS 17. The research proves that leadership style, independence and understanding of good governance affect the performance of internal auditors. Another finding is that the understanding of good governance has a significant effect on the performance of internal auditors with the lokal culture of the Sasak tribe as a moderating variable. This is because a good understanding of good governance will improve the performance of auditors so that organizational goals can be achieved. Keywords: Local Sasak Culture; Leadership Style; Independence; Understanding of Good Governance; Performance of the Inspectorate Auditor.